1966
DOI: 10.1161/01.cir.34.5.774
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of the Atrioventricular Conduction System in Ventricular Septal Defect and Tetralogy of Fallot: Correlations with the Electrocardiogram and Vectorcardiogram

Abstract: IN RECENT YEARS the morphological features of the major portions of the atrioventricular (A-V) conduction system of human hearts that were afflicted with various congenital anomalies have been described. [1][2][3][4][5][6] These reports have contrasted the anatomy of the A-V conduction system in examples of ventricular septal defect (VSD) and tetralogy of Fallot with that configuration found in defects of the persistent atrioventricular (A-V) canal type.7 8The vectorcardiographic (VCG) pattern found in the A-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…64 In adults, baseline sinus rhythm is the rule, with P waves of normal axis, duration, and amplitude, although somewhat peaked. 67 The QRS axis is typically normal or displaced to the right with right ventricular hypertrophy. In the presence of a right bundle-branch block, criteria for right ventricular hypertrophy include an RЈ in V 1 Ն15 mm and right-axis deviation of the initial vector representing unblocked forces.…”
Section: Surgically Corrected Tetralogy Of Fallotmentioning
confidence: 99%
See 2 more Smart Citations
“…64 In adults, baseline sinus rhythm is the rule, with P waves of normal axis, duration, and amplitude, although somewhat peaked. 67 The QRS axis is typically normal or displaced to the right with right ventricular hypertrophy. In the presence of a right bundle-branch block, criteria for right ventricular hypertrophy include an RЈ in V 1 Ն15 mm and right-axis deviation of the initial vector representing unblocked forces.…”
Section: Surgically Corrected Tetralogy Of Fallotmentioning
confidence: 99%
“…68 Left-axis deviation should raise suspicion for an associated AVCD, although left anterior hemiblock is present in 5% to 10% of adults. 67 Right bundle-branch block is expected after repair, even in the absence of a ventriculotomy incision. 67 Early QRS lengthening after repair results from surgical injury to the right bundle branch and myocardium, 69 whereas later broadening reflects right ventricular dilation.…”
Section: Surgically Corrected Tetralogy Of Fallotmentioning
confidence: 99%
See 1 more Smart Citation
“…These workers had earlier shown similar patterns of origin of the left bundle branch in hearts with isolated VSDs and Fallot's tetralogy exhibiting a superior axis. In these hearts they again concluded that the distribution of the left bundle branch favoured initial activation of the posterior septum (Feldt, DuShane, and Titus, 1966). Few detailed studies of the conduction tissue have been made in the other anomalies presently studied which possessed superior axes.…”
Section: Normalmentioning
confidence: 90%
“…The defect displaces the conducting elements posteriorly so that they ramify as a continuous sheet, mainly over the posterior septum. The position of the conducting tissue is based on personal sttudies (R. H. Anderson, unpublished observations), together with the works of Feldt et al, 1966, and Demoulin and Kulbertus (1972. posteriorly by the defect, and that the left bundle branch was distributed principally to the posterobasal portion of the septum (Fig.…”
Section: Normalmentioning
confidence: 99%